In vitro phytochemical, antioxidant activity and antimycobacterial potentials of selected medicinal plants commonly used for respiratory infections and related symptoms in the Limpopo Province, South Africa - Maphuti S. Matlala; Kgabo L. M. Moganedi; Peter Masoko (BMC Complementary Medicine and Therapies)
Abstract Background The emergence of drug resistance among Mycobacterium tuberculosis (Mtb) strains, coupled with the detrimental side effects linked to tuberculosis (TB) treatment, underscores the persistence of TB as a significant clinical and public health concern in South Africa, thereby necessitating ongoing research in drug discovery. The use of medicinal plants for the treatment of TB has garnered increasing attention, especially in countries where a significant portion of the population relies on traditional medicine as a primary form of healthcare. Methods The crude extracts from nine medicinal plants were investigated for antimycobacterial activity. Phytochemical profiling and qualitative antioxidant activity were assessed using thin layer chromatography. The 2,2-Diphenyl-1-picrylhydrazyl radical scavenging assay was used for quantitative antioxidant analysis. The broth microdilution assay was used to determine the antimycobacterial activity of the plant extracts and rifampicin against Mycobacterium smegmatis (ATCC 1441). Sodium dodecyl polyacrylamide gel electrophoresis was used to qualitatively evaluate the protein profile of M. smegmatis. The growth response of M. smegmatis to both inhibitors (rifampicin and plants extracts) was assessed through growth kinetics assays. Results Phytochemical profiling revealed that all plants contained various phytoconstituents in differing concentrations. Additionally, the plants exhibited relatively low antioxidant activity, as indicated by their IC50 values. Rosmarinus officinalis and Zanthoxylum capense demonstrated inhibitory effects on the growth of M. smegmatis with a minimum inhibitory concentration of 0.625 mg/ml. The time-kill assays indicate that the plant extracts including those of Gardenia volkensii, Citrus lemon, Croton gratissimus and Clerodendrum glabrum exhibited greater growth reduction than rifampicin. Sodium dodecyl polyacrylamide gel electrophoresis profiles revealed distinct patterns of M. smegmatis proteins. Protein profiles suggest that plant extracts, like rifampicin, affect bacterial protein synthesis. Conclusion The results of this study indicate that the plants do not have potent free radical scavenging capabilities. Nevertheless, they exhibited antimycobacterial properties, notably impacting protein synthesis.